2017
DOI: 10.18632/oncotarget.23138
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection is an independent prognostic factor in follicular lymphoma

Abstract: Hepatitis C virus (HCV) is a single-stranded RNA virus that not only affects hepatocytes, by B cells as well. It is thought that HCV is involved in the onset of B-cell lymphoma. The clinicopathological characteristics of HCV-positive diffuse large B-cell lymphoma (DLBCL) and HCV-positive splenic marginal zone lymphoma (SMZL) are known, but there has been no report on HCV-positive follicular lymphoma (FL). In this study, the clinicopathological characteristics of HCV-positive FL were examined in 263 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…A recently reported study from Japan including 10 HCV‐infected patients with FL found that HCV‐infected patients had higher Ann Arbor stages, FLIPI scores, and number of lymph nodes involved compared to HCV‐uninfected patients with FL 19 . We did not find such differences in our study, possibly because our study was conducted in a tertiary cancer center, where patients with more advanced FL are typically referred.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A recently reported study from Japan including 10 HCV‐infected patients with FL found that HCV‐infected patients had higher Ann Arbor stages, FLIPI scores, and number of lymph nodes involved compared to HCV‐uninfected patients with FL 19 . We did not find such differences in our study, possibly because our study was conducted in a tertiary cancer center, where patients with more advanced FL are typically referred.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, we showed for the first time that A recently reported study from Japan including 10 HCV-infected patients with FL found that HCV-infected patients had higher Ann Arbor stages, FLIPI scores, and number of lymph nodes involved compared to HCV-uninfected patients with FL. 19 We did not find such differences in our study, possibly because our study was conducted in a tertiary cancer center, where patients with more advanced FL are typically referred. However, we did find that HCV-infected patients had a higher rate of splenic involvement of FL than HCV-uninfected patients had, in agreement with our previous studies showing a higher rate of splenic involvement in HCV-infected patients with DLBCL 20,21 and with earlier reports showing high rates of HCV seropositivity in patients with B-cell NHL involving the spleen.…”
Section: Discussionmentioning
confidence: 61%
“…9 Is HCV elimination associated with better outcome in FL patients is unclear and subject of discussion. The recent studies demonstrated that the HCV-positive vs HCV-negative FL patients had significantly worse outcome (3-year OS 40% vs 90%, P < .0001 and relapse-free survival 30% vs 60%, P = .006) 6 and HCV-infected patient with FL successfully treated had a better 10-year OS rate than did cases not treated with antivirals. 11 In our study, there were no HCV-untreated FL patients as a comparison (since this is impossible now due to curative treatment), but we did not find differences in survival in a comparable group of FL patients without HCV observed over the same…”
mentioning
confidence: 99%
“…Nesterova et al (31) found a non-significant difference in the outcome of 11 patients with FL and HCV infection who received sofosbuvir-based combination concomitant with immune-chemotherapy compared to patients with FL without HCV infection, which is the same in our study. The old studies demonstrated that the HCV-positive vs HCV-negative FL patients had significantly worse outcome (3-year OS 40% vs 90%, P < .0001 and relapse-free survival 30% vs 60%, P = .006) (35) . The only comparative study (31) conducted to compare the outcome of HCV positive lymphoid malignancies treated using DAAs concomitantly with chemotherapy versus HCV negative lymphoid malignancies had the same results as our study.…”
Section: Discussionmentioning
confidence: 99%